Effect of Combination Hemodialysis Hemoperfusion on Lowering Leptin Level in Patients with Kidney Failure Receiving Routine Hemodialysis: A Multi-Center Study - Naraswari, Ilsya Asti; Puspitasari, Metalia; Wardhani, Yulia (Acta Interna The Journal of Internal Medicine, 2024)
Background: Leptin clearance during conventional haemodialysis (HD) has been found to be minimal or absent. Some authors reported the possibility of decreasing leptin serum levels with high flux membranes, but limited date are available. Leptin has been reported as a marker of inflammation and long-term complications such as cardiovascular events leading to increased quality of life deterioration. Haemodialysis hemoperfusion (HD+HP) has been reported to effectively decrease middle-sized and macromolecular toxin concentrations. In the present study, we compared the effectiveness of high-flux HD and HD + HP can effectively remove serum leptin levels, and is expected to reduce cardiovascular events in patients with kidney failure.Objective: To assess the influence of HD+HP therapy on serum leptin level in routine haemodialysis patients.Metode: Quasi experimental with pre and post exposure measurements in 26 kidney failure patients who received routine HD at three hospital sites were selected according to inclusion criteria and divided into intervention group (HD twice a week + Hemoperfusion once a week) and control group (HD twice a week). Serum leptin levels were compared before and after 8 weeks of therapy, and differences were then compared from each group.Result: Leptin levels reduced significantly (p = 0.017) in the control group (High-Flux HD). Serum leptin levels decreased in HD+HP group but there was no significant differences (p = 0.784). Significant differences were not observed between two modalities (HD and HD+HP) (p = 0.258).Conclusion: Haemodialysis plus hemoperfusion once a week for 8 weeks was not found effectively lowering leptin level compared high-flux HD alone.